2005
DOI: 10.1007/s10443-005-1123-5
|View full text |Cite
|
Sign up to set email alerts
|

High Strain Rate Response of Sandwich Composites with Nanophased Cores

Abstract: Polyurethane foam materials have been used as core materials in a sandwich construction with S2-Glass/SC-15 facings. The foam material has been manufactured from liquid polymer precursors of polyurethane. The precursors are made of two components; part-A (diphenylmethane diisocyanate) and part-B (polyol). In one set of experiments, part-A was mixed with part-B to manufacture the foam. In another set, TiO 2 nanoparticles have been dispersed in part-A through ultrasonic cavitation technique. The loading of nanop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…As the foams had close foam densities and were fabricated in identical closed molds, the PUF/CCS composites with a smaller cell size had to have a thinner cell edge than the neat foam. This was confirmed by the SEM micrographs shown in Figure 7(a–c), which show that the cross‐sectional areas of the cell edges were 914 μm 2 for the neat PUF and 593 and 402 μm 2 for the PUFs with 2.3 and 4.6 wt % concentrations of CCSs, respectively 20…”
Section: Resultssupporting
confidence: 65%
“…As the foams had close foam densities and were fabricated in identical closed molds, the PUF/CCS composites with a smaller cell size had to have a thinner cell edge than the neat foam. This was confirmed by the SEM micrographs shown in Figure 7(a–c), which show that the cross‐sectional areas of the cell edges were 914 μm 2 for the neat PUF and 593 and 402 μm 2 for the PUFs with 2.3 and 4.6 wt % concentrations of CCSs, respectively 20…”
Section: Resultssupporting
confidence: 65%
“…In this aspect, ultrasonication is an alternative to high-speed mixers and agitator bead mills. Ultrasonication has been used as a technique to disperse nanomaterials in different matrices [26][27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…The materials used for manufacturing the sandwich composite with nanophased foam are shown in Table 1. Manufacturing procedure of sandwich composites with nanophased core is discussed elaborately in our previous work [11]. However, in brief, nanophased polyurethane foam was fabricated in two steps-the first step was the dispersion of nanoparticles (via sonication) into liquid polyurethane, and the second was the casting of foam.…”
Section: Methodsmentioning
confidence: 99%
“…As both neat and nanophased foams have similar densities [11] and they are fabricated in identical closed molds, nanophased foam with larger cell size must have thicker cell edge, wall, or faces than those of the neat foam. This is confirmed by SEM micrographs shown in Figure 4 where it is found that cell wall thickness in nanophased foam is 7.4 μm whereas in neat polyurethane foam, it is 3.86 μm.…”
Section: Microstructural Propertiesmentioning
confidence: 99%
See 1 more Smart Citation